2020
DOI: 10.1038/s41598-020-74423-z
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of the regulation of ester balance between oxidation and esterification in aged Baijiu

Abstract: The influence of oxidation and esterification on the ester balance of aged Baijiu and methodology for the rational design of liquor flavors to optimize the practice of Baijiu production are not completely understood. We investigated the influence of ester balance on the flavor compounds of aged Baijiu by conducting constituent analysis of Baijiu from different aging times (0, 1, 2, 3, 4, 5, and 10 years). The changes of the main flavor compounds in the aging process were determined, and the correlations among … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 22 publications
0
22
0
Order By: Relevance
“…3 c. As seen, the content of lactic acid decreased steadily along with the increase of processing time of electrochemical treatment, while the content of ethyl lactate increased steadily along with the increase of processing time, which confirmed the transformation from lactic acid to ethyl lactate by the esterification process. In the earlier publication it was found that the spontaneous oxidation in the Baijiu aging process contributed to the increase of ester content ( Deng et al, 2020 ). The reaction rate of spontaneous oxidation, caused by the dissolved oxygen, is extremely slow, and a long period of time (at least three years) is required for the Baijiu aging process.…”
Section: Resultsmentioning
confidence: 99%
“…3 c. As seen, the content of lactic acid decreased steadily along with the increase of processing time of electrochemical treatment, while the content of ethyl lactate increased steadily along with the increase of processing time, which confirmed the transformation from lactic acid to ethyl lactate by the esterification process. In the earlier publication it was found that the spontaneous oxidation in the Baijiu aging process contributed to the increase of ester content ( Deng et al, 2020 ). The reaction rate of spontaneous oxidation, caused by the dissolved oxygen, is extremely slow, and a long period of time (at least three years) is required for the Baijiu aging process.…”
Section: Resultsmentioning
confidence: 99%
“…Fruity-like volatile compounds take an important part in the correlation network, including 2-butanol, ethyl propanoate, ethyl isobutyrate, ethyl hexadecenoate, isoamyl acetate, and isobutanol, which were all correlated to furfural, and the average abundance of these compounds in the RG group were all higher than that in the RP group. It is worth noting that due to the esterification and hydrolyzation balance of ester/acid in SAB [ 36 ], a close association between several pairs of ester/acid in the correlation network was noticed, for example, the correlation between acetic acid and ethyl acetate, and the correlation between butyric acid and ethyl butyrate.…”
Section: Resultsmentioning
confidence: 99%
“…Ethyl acetate, one of the most abundant esters in Baijiu, 40 has a low boiling point and high volatilization. Because of the volatilization and the partial hydrolysis of ethyl acetate, the amount of ethyl acetate in Baijiu decreases rapidly with aging, 41 which could be associated with the decreased pungency and the improved smoothness with aging of Baijiu.…”
Section: ■ Results and Discussionmentioning
confidence: 99%